Women’s Language Features on The Upper Class Female Characters of The Great Gatsby Movie - Victoria Utomo, Tamara (Udayana Journal of Social Sciences and Humanities, 2022)
This study is entitled Women’s Language Features on The Upper Class Female Characters of The Great Gatsby Movie. There are two aims of this study: identifying the type of women’s language features on the upper class female characters of The Great Gatsby and the sociological function that influenced the characters to use the feature. The data were taken from a movie entitled The Great Gatsby that was released in 2013. There are three characters whose utterances were analysed in this movie: Daisy, Jordan, and Daisy’s mother. The data was gathered from the movie by watching the movie through an online movie streaming service and reading the script. Qualitative research method was used to collect the data. Then the data was analysed mainly with women’s language theory by Robin Lakoff and supported with other theories and opinions from numerous experts in this field. There are seven out of ten women’s language features found in the female characters’s utterances of this movie. The features are lexical hedges, empty adjectives, tag question, intensifier, avoidance of swear words, rising intonation on declaratives and emotional emphasis. There is also an analysis on how their social class may have been the influence in the amount of women’s language features they used in their utterances.